HUBUNGAN AKTIVITAS SPIRITUAL DENGAN KUALITAS HIDUP PASIEN MUSLIM DENGAN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RUMAH SAKIT ISLAM IBNU SINA PEKANBARU - Samsul " Bahri; Bayhakki " "; Riri " Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Activity of spiritual is all religious activity concerning praying, fasting, and reading Al-Quran. This research aimed to identify the relationship of spiritual with the quality of life moslem patient in chronic renal failure experiencing hemodialysis in Islamic Hospital Ibnu Sina Pekanbaru. The design used in this research was descriptive correlational with cross-sectional approach. This research was conducted in hemodialysis unit involving 50 respondents. Sampling method used total sampling. Measuring tool used was questionnaire that has been examined for it’s validity and reliability. The research result indicated that majority of activity of spiritual was as much as 21 respondents (42%), 17 respondents (34%) experiencing of the quality of good life and 3 respondents (6%) experiencing intermediate quality of life and 1 respondents (2%) experiencing bed quality of life. The chi-square test result showed p value (0,002) < α (0,05), so that there was relation between activity of spiritual with quality of life of moslem patient with chronic renal failure experiencing hemodialysis. Result of this research was expected can be concern to hospital to improve the quality of service for moslem patient with chronic renal failure experiencing hemodialysis. Keywords: Activity of spiritual, chronic renal failure, hemodialysis, quality of life